Estudio bibliométrico de la biblioteca de la Real Sociedad Económica Extremeña de Amigos del País. Parte I. Colección de los siglos XVI-XVIII - Pulgarín Guerrero, Antonio; Marroquín Martínez, Laura; Herrera Morillas, José Luís (Revista General de Información y Documentación, 2008)
The aim of this paper is to study and to report globally on the stock of antiquarian books at the Library of the “Real Sociedad Económica Extremeña de Amigos del País” (Royal Extremaduran Economic Society of Friends of the Country). A recopilation of bibliographic data on this stock corresponding to the 16th, 17th and 18th centuries has been made. These data are organized for processing and quantitative analysis, and are contrasted with the Collective Catalogue of Spanish Bibliographic Patrimony (C.C.P.B.E.) to determine the extent of the singularity or rareness of the stock (the data from the R.E.E.S.F.C. library are not included in the C.C.P.B.E.). The results are analysed and interpreted to reflect and highlight the role played by Economic Societies of the Country. The stock studied is: 13 books from the 16th century, 39 from the 17th, and 566 from the 18th century. The evolution of the number of books is analysed, together with the productivity of the authors, place of edition, distribution of books by printer, and distribution by subject. There is also an indication of the number of books deposited as unique (in relation to the C.C.P.B.E.) in the Library.